The Power of Transformative Relational Marketing of Batik MSMEs in Banyumas and Purbalingga Regencies - SHAFERI, INTAN; Tri Nawarini, Alisa; Pradipta Setyanto, Refius (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
The power of transformative relational marketing for MSMEs is a reflect of how the performance of an entity. MSMEs are conducting the obligation to have good capacity in their performance. MSMEs batik is on of the growth sector. The current relational management aspect for MSMEs batik give alternate of combination aspects from entrepreneurial orientation, network capability, and response speed of the Batik MSMEs relational marketing. This study aims to examine the effect of entrepreneurial orientation, network capability, and response towards the transformative relational marketing. This research was taken place of Batik SMEs in Banyumas and Purbalingga Regencies, used the dependent variable of power of transformative relational marketing and the independent variables of partner network capability, entrepreneurial orientation, and customer response speed. This study used 120 MSME respondents in Banyumas and Purbalingga Regencies during January until June 2022. Analysis SEM PLS was used in this study. The results of the entrepreneurial orientation, partner network capability, and the response speed effect transformative relational marketing.